SWMM modeling of water sensitive urban design : Dry detention pond for residential estate - Afdal Haziq, Mohammad Salehe (Universiti Malaysia Sarawak, UNIMAS, 2013)
Dry ponds which are also called detention ponds are stormwater basins that are designed to intercept volume of stormwater runoff and temporarily impound the water for gradual release to the receiving stream or waterways. This thesis is to analyze the application of dry pond as a Water Sensitive Urban Design in Taman Casa Marbella, Tabuan Laru, Sarawak, Malaysia using Storm Water Management Model (SWMM). SWMM is used to estimate runoff in storm water drainage components. Three different scenarios are developed, which are first, directly uncontrolled runoff, secondly dry pond, and thirdly dry pond with underground detention storage. The modeling output has determined that the peak discharge of using detention pond is 48% lower than the uncontrolled or direct discharge. Furthermore, 0.9m deep underground storage is expected to fully detend runoff from 10-years ARI storm. But with MSMA recommendations, 0.6m deep dry pond with 0.4m underground storage is found to be the most suitable design.